(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article explores the interrelated concepts of recognition, dignity, and social inclusion, emphasizing their philosophical and social significance. Recognition is understood as the acknowledgment of an individual’s or group’s inherent value, while dignity reflects the moral worth that underpins human rights and ethical treatment. Social inclusion involves creating equitable opportunities for participation in social, economic, and political life. The paper argues that recognition and dignity are essential prerequisites for meaningful inclusion, as exclusion often results from the denial of respect, identity, or voice. Drawing on contemporary social theory, philosophical perspectives, and case studies of marginalized groups, the article highlights how policies, social practices, and cultural attitudes can foster or hinder inclusive societies. By linking ethical principles with practical frameworks, the study contributes to a more holistic understanding of social inclusion and its role in promoting justice, equality, and human flourishing.